Hydrothermal Dissolution of Deeply Buried Cambrian Dolomite Rocks and Porosity Generation: Integrated with Geological Studies and Reactive Transport Modeling in the Tarim Basin, China. (4th May 2017) - Wei, Wenwen; Chen, Daizhao; Qing, Hairuo; Qian, Yixiong
Abstract : The burial dissolution of carbonate rocks has long been an interesting topic of reservoir geologists. Integrated with geological studies and reactive transport modeling, this study investigated the Cambrian dolomites that were buried at depths up to 8408 m and still preserved a large amount of unfilled dissolution vugs from the borehole TS1 in the northern Tarim Basin. Studies indicate that these vugs were formed in association with fault-channeled hydrothermal fluids from greater depth through "retrograde dissolution" as the fluid temperature dropped during upward migration. The reactive transport modeling results suggest an important control of the vertical permeability of wall-rock on fluid and temperature patterns which, in turn, would control the spatial distribution of dissolving-originated porosity. The hydrothermal dissolution mainly occurred in dolomite wall-rocks with higher vertical permeability (extensive development of tensional fractures and connected pore spaces), producing additional dissolved porosity there during deep burial. This study implicates the importance of multidisciplinary approaches for understanding the burial/hydrothermal dissolution of dolomite rocks and predicting favourable deep/ultradeep carbonate reservoirs.